Eccentrically-compressed reinforced concrete columns strengthened with partial jacketing - Oliveira, Denio Ramam Carvalho de; Branco, Vitor Lopes; Damasceno, Iana Ingrid Rocha (Revista ALCONPAT, 2018)
The behavior of six uniaxial compression columns is investigated. Specimen featured an initial section of (120 x 200) mm2, a final section of (200 x 200) mm2 and height of 1.600 mm, strengthened on the tensile and compression sides with plaster or not. Adherence between new and old concrete, and cracking pattern was satisfactory. Although coated columns showed the same behavior to their respective non-coated ones even when concrete area was reduced by approximately 20%, problems consisted in the crushing of the reinforced concrete layer immediately prior to the rupture of the columns. This strengthening proved to be more adequate when undertaken at the columns´ compressed zone and may be executed through conventional procedures with or without mortar coating layer.